Pragmatic Analysis of Maxims Flouting Contained in PunHubOnline Memes on Instagram - Alifa Fegasanti, Prahda; Pratama, Hendi; Wahyuni, Sri (English Education Journal, 2025)
The massive use of the internet in Indonesia is followed by the use of social media. This gave birth to a new phenomenon among its users, the creativity of making memes. Memes in the form of images or videos are defined as ideas, behaviors or styles that spread from one person to another through social media which become a vehicle for entertainment due to their funny and parodic nature. Humor in memes can occur because speakers are flouting Grice's Cooperative Principle. This study aims to describe how the flouting maxim in PunHubOnline memes and how the strategy used to produce implicature. The results show that these funny memes are generated by flouting Grice's maxim where exaggeration or under-statement is often created through the implicature of flouting the maxim. Flouting of Quantity maxims often occurs because the information provided contains more and less, while in flouting of quality maxims it often occurs due to several strategies namely hyperbole, metaphor, Irony and Banter. Flouting of relevance maxims also occurs when the conversation in the meme contains irrelevant conversations between speakers and speech partners. In addition, flouting maxim of manner often occurs due to being obscure in the conversation in the meme.